Expansion and evolution of insect GMC oxidoreductases. - Iida, K.; Cox-Foster, D.L.; Yang, X.; Ko, W.; Cavener, D.R. (BMC Evolutionary Biology, 2007)
The GMC oxidoreductases comprise a large family of diverse FAD enzymes that share a homologous backbone. The relationship and origin of the GMC oxidoreductase genes, however, was unknown. Recent sequencing of entire genomes has allowed for the evolutionary analysis of the GMC oxidoreductase family.Although genes that encode enzyme families are rarely linked in higher eukaryotes, we discovered that the majority of the GMC oxidoreductase genes in the fruit fly (D. melanogaster), mosquito (A. gambiae), honeybee (A. mellifera), and flour beetle (T. castaneum) are located in a highly conserved cluster contained within a large intron of the flotillin-2 (Flo-2) gene. In contrast, the genomes of vertebrates and the nematode C. elegans contain few GMC genes and lack a GMC cluster, suggesting that the GMC cluster and the function of its resident genes are unique to insects or arthropods. We found that the development patterns of expression of the GMC cluster genes are highly complex. Among the GMC oxidoreductases located outside of the GMC gene cluster, the identities of two related enzymes, glucose dehydrogenase (GLD) and glucose oxidase (GOX), are known, and they play major roles in development and immunity. We have discovered that several additional GLD and GOX homologues exist in insects but are remotely similar to fungal GOX.We speculate that the GMC oxidoreductase cluster has been conserved to coordinately regulate these genes for a common developmental or physiological function related to ecdysteroid metabolism. Furthermore, we propose that the GMC gene cluster may be the birthplace of the insect GMC oxidoreductase genes. Through tandem duplication and divergence within the cluster, new GMC genes evolved. Some of the GMC genes have been retained in the cluster for hundreds of millions of years while others might have transposed to other regions of the genome. Consistent with this hypothesis, our analysis indicates that insect GOX and GLD arose from a different ancestral GMC gene than that of fungal GOX.